A new perspective on cardiovascular function and dysfunction during endurance exercise: identifying the primary cause of cardiovascular risk - Amine Souissi; Ismail Dergaa; Samia Ernez Hajri; Karim Chamari; Helmi Ben Saad (Biology of Sport)
Exercise mechanical efficiency typically falls within the range of approximately 20 to 25%. This means that a great part of the metabolic energy converted to generate movement is released as heat. Therefore, the rise in core temperature during endurance exercise in humans is proportional to generated work. Cutaneous vasodilation occurs when the core temperature threshold is reached. The rise in heart rate in response to thermal stress is a cardiovascular response that increases cardiac output and skin blood flow. The cardiovascular response during endurance exercise is a complex phenomenon potentially influenced by the involvement of nitric oxide in active thermoregulatory vasodilation. Excessive exercise can create high oxidative stress by disrupting the balance between free radicals’ production and scavenging, resulting in impaired cardiovascular function. The above considerations are related to the severity and duration of endurance exercise. The first focus of this narrative review is to provide an updated understanding of cardiovascular function during endurance exercise. We aim to explore the potential role of oxidative stress in causing cardiovascular dysfunction during endurance exercise from a fresh perspective. Additionally, we aim to identify the primary factors contributing to cardiovascular risk during strenuous prolonged exercise by highlighting recent progress in this area, which may shed light on previously unexplained physiological responses. To ascertain the effect of endurance exercise on cardiovascular function and dysfunction, a narrative review of the literature was undertaken using PubMed, ScienceDirect, Medline, Google Scholar, and Scopus. The review highlighted that high oxidative stress (due to high levels of catecholamines, shear stress, immune system activation, and renal dysfunction) leads to a rise in platelet aggregation during endurance exercise. Importantly, we clearly revealed for the first time that endothelial damage, vasoconstriction, and blood coagulation (inducing thrombosis) are potentially the primary factors of cardiovascular dysfunction and myocardial infarction during and/or following endurance exercise.